2011
DOI: 10.1109/tdmr.2010.2068572
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Near-Surface Thermal Stresses on Interfacial Reliability of Through-Silicon Vias for 3-D Interconnects

Abstract: Abstract-Continual scaling of on-chip wiring structures has brought significant challenges for materials and processes beyond the 32-nm technology node in microelectronics. Recently, 3-D integration with through-silicon vias (TSVs) has emerged as an effective solution to meet the future interconnect requirement. Among others, thermomechanical reliability is a key concern for the development of TSV structures used in die stacking as 3-D interconnects. This paper examines the effects of thermally induced stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 245 publications
(108 citation statements)
references
References 23 publications
2
102
0
Order By: Relevance
“…Via extrusion, or pop-up, is a reliability issue in 3D integration in which Cu extrudes from the wafer surface to damage the interconnect structures above the vias [5]. A previous study has shown that stress-induced interfacial delamination could result in via extrusion [7]. However, in subsequent investigations including this study, via extrusion was observed without evidence of delamination.…”
Section: Local Plasticity and Via Extrusionmentioning
confidence: 61%
See 2 more Smart Citations
“…Via extrusion, or pop-up, is a reliability issue in 3D integration in which Cu extrudes from the wafer surface to damage the interconnect structures above the vias [5]. A previous study has shown that stress-induced interfacial delamination could result in via extrusion [7]. However, in subsequent investigations including this study, via extrusion was observed without evidence of delamination.…”
Section: Local Plasticity and Via Extrusionmentioning
confidence: 61%
“…Thermal stresses can arise during fabrication, testing and operation of the TSV structures due to the large mismatch in the coefficient of thermal expansion (CTE) between Cu and Si. The stresses are large enough to cause serious reliability concerns even structural failures in the integrated structure, including TSV extrusion, cracking of Si near the TSV and degradation of device performance [5][6][7][8][9]. Management and mitigation of thermal stresses in the TSV structures require proper stress characterization and modeling analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between two opposite thermal loads is further illustrated in Figure 2. The analytical solutions for steady-state TSV delamination have been derived for both the cooling and heating conditions [6]. Consider an isolated, infinitely long TSV embedded in an infinite matrix with a circumferential crack propagating along the axial direction under a thermal load.…”
Section: Crack Driving Force For Tsv Delamination: Steady-state Solutmentioning
confidence: 99%
“…Based on the results from the microstructure analysis, the mechanisms underlying the linear and nonlinear temperature-curvature behavior of the TSV specimen are discussed. The local stress distribution near the Si surface around the Cu vias is important on device performance and interfacial reliability [7,8]. This was measured by micro-Raman spectroscopy [9].…”
Section: Introductionmentioning
confidence: 99%